The Role of Communication in Ethnic–Political Conflicts (Annual of the Faculty of Philosophy in Skopje, 2017)
This paper analyses the communication role within the framework of ethnic- political conflicts. Therefore, the paper analyses if and what is the communication process influence in understanding of ethnic-political conflicts, as well as its influence in their resolution. Traditional conflict resolution usually seeks to produce acceptable political agreements, as instruments of conflict solving. Still, new patterns of communication between rivals (e.g. micro-level of communication) draw attention to some new issues and influences. Most of these new influences are devoted to changing relationships rather than producing agreements. Actually, this is an approach to conflict resolution that requires long-term communicative contact, in order to achieve more stable and cooperative relationships. Starting from this point of view, this paper focuses on ethnic- political conflict characteristics (including their theoretical aspects, causes, consequences and efforts to solve them), as well as on the communication significance in their understanding and resolution. Therefore, the paper analyses the micro and macro level of communication influence, related to this issue.
Keywords: COMMUNICATION; IDENTITY; ETHNIC GROUPS; ETHNIC- POLITICAL CONFLICT